Tyrosine phosphorylation is required for activation of an alpha interferon-stimulated transcription factor. - Gutch, M J (1992)
The signal transduction pathway of alpha interferon utilizes tyrosine phosphorylation to transmit a signal generated at the cell surface to the transcriptional machinery in the nucleus. Activation of the interferon pathway initiates with the binding of alpha interferon to its cell surface receptor. The ligand-receptor complex signals the activation of a latent cytoplasmic transcription factor. The active form of the interferon-stimulated gene factor (ISGF3) is phosphorylated on tyrosine residues. ISGF3 subsequently translocates to the nucleus and binds to a DNA sequence, the interferon-stimulated response element, found within the promoter of inducible genes. ISGF3 is a multicomponent factor consisting of four proteins of 113 kDa, 91 kDa, 84 kDa, and 48 kDa. Three proteins consistent with sizes of 113 kDa, 91 kDa, and 84 kDa copurify with ISGF3 and are phosphorylated on tyrosine residues after stimulation by alpha interferon. Tyrosine phosphorylation is essential for activation of ISGF3. Genistein, a tyrosine kinase inhibitor, blocks the appearance of ISGF3 and blocks the transcriptional stimulation of interferon-induced genes. This study shows that tyrosine phosphorylation provides a link between the interferon-receptor complex at the plasma membrane and specific activation of gene expression in the nucleus.